Aceite esencial de origen vegetal como potencial controlador del gorgojo Pagiocerus frontalis en maíz blanco almacenado - Herrera Armijos, Osmany Manuel (2024)
In the Andes region, white maize (Zea mays) is traditionally one of the key foods. This grass is grown during the rainy season and stored for future use; in small units of stored maize grains in cold climates, the weevil Pagiocerus frontalis is the most important pest, causing more than 30% of losses. Synthetic insecticides are used for its control, but these represent serious problems for human health, affect the environment, and have created resistance in several insect pest species. Here, the chemical composition of the essential of Ruta graveolens and Ocotea quixos was extracted, evaluated, and their activities against Pagiocerus frontalis were evaluated. Chromatographic analysis revealed that the essential oil of Ocotea quixos is mainly composed of ο-Cymene (25.87%); α-Pinene (14.09%); and 1, 8-Cineole (6.91), on the other hand the major components of Ruta graveolens are 2-Nonanone (45.80%); and 2-Undecanone (42.47%). The essential oils of Ocotea quixos LC50 = 126.14 [122.34 – 130.02] μL/L-1 and, for Ruta graveolens LC50 = 153.37 [143.55 – 164.30] μL/L-1 , being toxic for adults of Pagiocerus frontalis. The essential oil of Ocotea quixos was repellent to adults of Pagiocerus frontalis when exposed for 24h, except at the concentration LC10 88.30 μL/L-1 ; (IR = 0.19) which did notshow significant difference with respect to the control. On the other hand, the essential oil of Ruta graveolens was able to repel the weevil, except at the concentration LC90 319.97 μL/L-1 ; (IR= 0.86) which did not show significant difference with the control. Overall, this study demonstrates that these essential oils could be successfully integrated into management programs against Pagiocerus frontalis.